Fiscal Policy Coordination Gains in a Monetary Union - Salvado, Susana (2021)
The objective of my PhD thesis is to understand how much can a Monetary Union gain if its fiscal policy were conducted in a coordinated way. My main conclusion is that fiscal policy coordination should be accounted in order to achieve an higher long term welfare level, but is not appealing as ashort-run mechanism for reacting to shocks. The main contribution of this work concerns the quantification of the fiscal coordination gain. Here, I combine the earlier notion of period-by-period coordination gain that was present in the literature of the 80's with the idea of stabilization that is present in the New-Keynesian literature. The main issue is that the latter analyses countries' reaction to shocks and the majority of its papers do not quantify any gains that might occur deriving from coordination of policies. Even when they quantify those gains, they do not rely on any reference measure. Hence, in this work I propose a straight-forward way to compare the gain. I compare the utility gain that occurs due to the reaction of shocks and the change in steady-states with the totality of the fiscal coordination gain. Another point worth mentioning is that the fiscal coordination gain that is considered throughout my work is not a by-product of any heterogeneity between countries. Instead, I assume that the countries that form the Monetary Union are identical and face the same distribution of shocks. The gain that occurs derives from strategical interaction among countries, namely in what entails changes in relative prices. Moreover, measuring the fiscal coordination gain is crucial since there are political, institutional and even commitment costs that might stem from the introduction of a coordinated fiscal policy in a Monetary Union. Therefore, the question is not about the existence or not of coordination gains, but how much the Union can gain if its fiscal policy is coordinated.